2022
DOI: 10.1038/s41598-022-12366-3
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology combined with GEO database identifying the mechanisms and molecular targets of Polygoni Cuspidati Rhizoma on Peri-implants

Abstract: Peri-implants is a chronic disease leads to the bone resorption and loss of implants. Polygoni Cuspidati Rhizoma (PCRER), a traditional Chinese herbal has been used to treat diseases of bone metabolism. However, its mechanism of anti-bone absorption still remains unknown. We aimed to identify its molecular target and the mechanism involved in PCRER potential treatment theory to Peri-implants by network pharmacology. The active ingredients of PCRER and potential disease-related targets were retrieved from TCMSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 86 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Then, we performed molecular docking on these drugs and the VPS16 protein, respectively. The molecular docking results showed that a total of 51 sensitive drugs spontaneously bound to the core target protein VPS16, and there were 19 drugs with strong molecular binding energy and binding energy less than -7 [ 21 ], among which the nine drugs with the strongest binding to VPS16 were ranked according to the binding energy; they were vinorelbine, cyclopamine, HG-6-64-1, midostaurin, OSU-03012, parthenolide, GSK-650394, BMS-509744, and dasatinib. The higher the binding energy, the closer the drug binds to VPS16.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we performed molecular docking on these drugs and the VPS16 protein, respectively. The molecular docking results showed that a total of 51 sensitive drugs spontaneously bound to the core target protein VPS16, and there were 19 drugs with strong molecular binding energy and binding energy less than -7 [ 21 ], among which the nine drugs with the strongest binding to VPS16 were ranked according to the binding energy; they were vinorelbine, cyclopamine, HG-6-64-1, midostaurin, OSU-03012, parthenolide, GSK-650394, BMS-509744, and dasatinib. The higher the binding energy, the closer the drug binds to VPS16.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the 3D docking results were visualized using PYMOL software and the 2D docking results were visualized using Discovery Studio software 2017. Among them, a docking score AFFINITY <-4.25 KCAL/MOL −1 considered a binding activity between ligand and target, a score <-5.0 KCAL/MOL −1 indicated a better binding activity, and a score <-7.0 KCAL/MOL −1 a strong docking activity between the two [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The GSE17351 datasets contained 5 normal samples and 5 tumor samples, the GSE26886 datesets contained 19 normal samples and 9 tumor samples, and the GSE161533 datesets contained 28 normal samples and 28 tumor samples, respectively. DEGs between ESCC patients with normal tissues and tumor tissues were obtained using the "limma" package of R 4.2.1 software according to the screening conditions of "adjusted P value < 0.05" and "|log 2 FC|> 1" [29] . The volcano plot and heat map of the DEGs from three gene chips were then plotted using the "ggplot2" and "pheatmap" package in the R software.…”
Section: Degs Of Esccmentioning
confidence: 99%